A Multi-Tracer Study of Fresh Water Sources for a Temperate Urbanized Coastal Bay (Southern Baltic Sea) - von Ahn, Cátia Milene Ehlert; Scholten, Jan C.; Malik, Christoph; Feldens, Peter; Liu, Bo; Dellwig, Olaf; Jenner, Anna-Kathrina; Papenmeier, Svenja; Schmiedinger, Iris; Zeller, Mary A.; Böttcher, Michael Ernst (Frontiers in Environmental Science, 2021)
Terrestrial surface waters and submarine ground water discharge (SGD) act as a source of dissolved substances for coastal systems. Solute fluxes of SGD depend on the ground water composition and the water-solid-microbe interactions close to the sediment-water interface. Thus, this study aims to characterize and evaluate the hydrogeochemical gradients developing in the fresh-salt water mixing zone of the Wismar Bay (WB), southern Baltic Sea, Germany. Sampling campaigns covering the WB, the fresh-salt water mixing zone at the beach of the WB shoreline, terrestrial surface and ground waters near the WB as well sediments pore water were carried out. In these different waters, the distribution of dissolved inorganic carbon, nutrients, major ions, trace elements, stable isotopes (H, O, C, S), and radium isotopes have been investigated. Enhanced concentrations of radium isotopes together with dissolved manganese, barium in the surface waters of the eastern WB indicated benthic-pelagic coupling via the exchange between pore water and the water column. Salinity, stable isotopes, and major ions in sediment pore water profiles identified the presence of fresh ground water below about 40 cmbsf in the central part of the bay. Geophysical acoustic techniques revealed the local impact of anthropogenic sediment excavation, which reduced the thickness of a sediment layer between the coastal aquifer and the bottom water, causing, therefore, a ground water upward flow close to the top sediments. The fresh impacted pore water stable isotope composition (δ18O, δ2H) plot close to the regional meteoric water line indicating a relatively modern ground water source. The calculated organic matter mineralization rates and the dissolved inorganic carbon sediment-water fluxes were much higher at the fresh impacted site when compared to other unimpacted sediments. Therefore, this study reveals that different fresh water sources contribute to the water balance of WB including a SGD source.